1994
DOI: 10.1017/s0890037x00028566
|View full text |Cite
|
Sign up to set email alerts
|

Spring Cereal Response to Imazamethabenz and Fenoxaprop-p-ethyl as Influenced by Environment

Abstract: The influence of temperature, soil moisture, and light intensity on the tolerance of spring wheat, durum wheat, and spring barley to imazamethabenz and safened fenoxaprop-p-ethyl was determined in growth chamber experiments. Imazamethabenz at 500 g/ha reduced plant height and shoot fresh weight of durum and spring wheats grown under prolonged 70% shade. The height of durum and spring wheats was reduced by imazamethabenz under a low temperature regime. Compared to the plants grown under standard conditions, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Four environmental regimes were established as follows (Xie et al 1994c). (1) the non-stressed (standard) regime was 20/15~ full light (400 ixE/m2/s) with a 16-h photoperiod, daily watering.…”
Section: General Proceduresmentioning
confidence: 99%
“…Four environmental regimes were established as follows (Xie et al 1994c). (1) the non-stressed (standard) regime was 20/15~ full light (400 ixE/m2/s) with a 16-h photoperiod, daily watering.…”
Section: General Proceduresmentioning
confidence: 99%
“…Negative effects were seen on wheat subjected to chlortoluron (Banting et al 1976), while no injury was observed when sulfosulfuron was applied on wheat exposed to different temperature cycles (25/238C vs. 5/38C) (Olson et al 2000). Other studies in cold chambers have been done on spring wheat (Xie et al 1994) or barley (McMullan 1994) exposed to one or two herbicides and the results were mixed, depending on the species and herbicide used. While providing interesting results, information from growth room/cabinet studies may not be transferable to field conditions.…”
mentioning
confidence: 99%
“…Husn. ], spring barley (Horduem vulgare L.) and spring wheat [16]. Reference [17] evaluated durum wheat sensitivity to various POST herbicides and found that injury of 3.4% to 4.9% and 1.9% to 8.0% was present 1 WAA when fenoxaprop-p-ethyl/safener was applied at a 1X and 2X rates, respectively.…”
Section: Resultsmentioning
confidence: 99%